Heritability of Apis mellifera recapping behavior and suppressed mite reproduction as resistance traits towards Varroa destructor - Gabel, Martin; Hoppe, Andreas; Scheiner, Ricarda; Obergfell, Jörg; Büchler, Ralph (Frontiers in Insect Science, 2023)
The selection of honeybee strains resistant to the ectoparasitic mite Varroa destructor is generally considered as one of the most sustainable ways of coping with this major bee parasite. Thus, breeding efforts increasingly focus on resistance parameters in addition to common beekeeping traits like honey yield and gentleness. In every breeding effort, the success strongly depends on the quantifiability and heritability of the traits accounted. To find the most suitable traits among the manifold variants to assess Varroa resistance, it is necessary to evaluate how easily a trait can be measured (i.e., testing effort) in relation to the underlying heritability (i.e., expected transfer to the following generation). Various possible selection traits are described as beneficial for colony survival in the presence of Varroa destructor and therefore are measured in breeding stocks around the globe. Two of them in particular, suppressed mite reproduction (SMR, sensu lato any reproductive failure of mother mites) and recapping of already sealed brood cells have recently gained increasing attention among the breeders because they closely resemble resistance mechanisms of some Varroa-surviving honeybee populations. However, it was still unknown whether the genetic background of the trait is sufficient for targeted selection. We therefore investigated the heritabilities and genetic correlations for SMR and REC, distinguishing between recapping of infested cells (RECinf) and all cells (RECall), on an extensive dataset of Buckfast and Carniolan stock in Germany. With an accessible h² of 0.18 and 0.44 for SMR and an accessible h² of 0.44 and 0.40 for RECinf, both traits turned out to be very promising for further selection in the Buckfast and Carnica breeding population, respectively.